Fra lek og tull - til toppidrett og VM-gull : Hva kjennetegner oppvekst, ulike støttespillere og psykologiske karaktertrekk hos en skiskytter som har nådd et høyt internasjonalt nivå? - Rui, M. (University of Agder, 2018)
The background for the present study is an interest in what makes the best athletes the best. Many intermediate athletes exercise as much as the best athletes in the world, so what determines which athlete achieve the best results? The purpose of the present study was to analyze different characteristics of a biathlete at a high international level, and to investigate the factors related to the early life and relationships that contributes to the athlete's performance development. The research question for the present study is; "what characterizes early life, significant others and psychological characteristics of a biathlete who has reached a high international level?". The study was conducted as a single case study, and one respondent was recruited based on defined inclusion criteria. Data were mainly collected through personal depth interviews with semi-structured interview guides. The recordings from the interviews were transcribed, data was structured, and categories emerged. Data was also collected utilizing questionnaires and observation to supplement data from the interviews. The results show that the respondent has several psychological characteristics that all contribute to achievement at a high international level. The characteristics that characterize the respondent are mental toughness, adaptive perfectionism, sports intelligence, high levels of high confidence, as well as appropriate sources of motivation. The respondent's early life and significant others throughout the career are also seen as factors that have contributed to the performance development of this athlete. The present study is a small contribution to the field of performance development within sports psychology. Indeed, the results seem to be transferable to the elite athlete context of other individual sports. However, more research is needed to investigate performance development in an elite sport context with a comprehensive perspective.